Anatomical Step-by-Step Dissection of Complex Skull Base Approaches for Trainees: Surgical Anatomy of the Far Lateral Approach - Graffeo, Christopher S.; Perry, Avital; Carlstrom, Lucas P.; Leonel, Luciano; Nguyen, Bachtri T.; Morris, Jonathan M.; Driscoll, Colin L. W.; Link, Michael J.; Peris-Celda, Maria (Journal of Neurological Surgery Part B: Skull Base, 2022)
Introduction Skull base neuroanatomy is classically taught using surgical atlases. Although these texts are critical and rich resources for learning three-dimensional (3D) relationships between key structures, we believe they could be optimized and complemented with step-by-step anatomical dissections to fully meet the learning needs of trainees.Methods Six sides of three formalin-fixed latex-injected specimens were dissected under microscopic magnification. A far lateral craniotomy was performed by each of three neurosurgery resident/fellow at varying stages of training. The study objective was the completion and photodocumentation of the craniotomy to accompany a stepwise description of the exposure to provide a comprehensive, intelligible, and anatomically oriented resource for trainees at any level. Illustrative case examples were prepared to supplement approach dissections.Results The far lateral approach provides a wide and versatile corridor for posterior fossa operation, with access spanning the entire cerebellopontine angle (CPA), foramen magnum, and upper cervical region.Key Steps Include The study includes the following steps: positioning and skin incision, myocutaneous flap, placement of burr holes and sigmoid trough, fashioning of the craniotomy bone flap, bilateral C1 laminectomy, occipital condyle/jugular tubercle drilling, and dural opening.Conclusion Although more cumbersome than the retrosigmoid approach, a far lateral craniotomy offers unparalleled access to lesions centered lower or more medially in the CPA, as well as those with significant extension into the clival or foramen magnum regions. Dissection-based neuroanatomic guides to operative approaches provide a unique and rich resource for trainees to comprehend, prepare for, practice, and perform complex cranial operations, such as the far lateral craniotomy.
Keywords: far lateral; meningioma; foramen magnum; lateral skull base; education; simulation; complex cranial surgery